2012
DOI: 10.1111/j.1551-2916.2012.05224.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Lithium Metasilicate Powders at Low Temperature via Mechanical Milling

Abstract: The Li2SiO3 powder has been successfully synthesized at low temperature via mechanical milling process. By using LiOH·H2O and tetraethyl orthosilicate (TEOS) as raw materials, Li2SiO3 powder with grain size of about 100 nm could be obtained at room temperature (~20°C) after mechanical milling for 120 h. This nano Li2SiO3 powder shows excellent thermal stability that no decomposing reaction or phase change would happen even after calcined at 900°C for 4 h. Experiments show that high concentration of the raw mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…As can be seen, the Li 2 CuO 2 structure was preserved in all the ball milled samples; however, the corresponding diffraction peaks became broader than those observed for the solid-state sample. Hence, these Li 2 CuO 2 microstructural variations are expected to induce important improvements in the CO 2 chemisorption process, as has been reported in previous papers for other lithium and sodium ceramics, [25][26][27][28][29][30][31]37 where the CO 2 chemisorption is importantly related to the particle size and surface area. The crystal size of the solid state sample was measured; however, it was larger than 500 A, which exceeds the detection limit.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…As can be seen, the Li 2 CuO 2 structure was preserved in all the ball milled samples; however, the corresponding diffraction peaks became broader than those observed for the solid-state sample. Hence, these Li 2 CuO 2 microstructural variations are expected to induce important improvements in the CO 2 chemisorption process, as has been reported in previous papers for other lithium and sodium ceramics, [25][26][27][28][29][30][31]37 where the CO 2 chemisorption is importantly related to the particle size and surface area. The crystal size of the solid state sample was measured; however, it was larger than 500 A, which exceeds the detection limit.…”
Section: Resultsmentioning
confidence: 55%
“…[26][27][28][29][30][31] Based on these results, it is clearly evident that the microstructural changes have important inuence at low and moderate temperatures during the CO 2 capture process in Li 2 CuO 2 . On the other hand, at high temperatures, the CO 2 chemisorption observed on the ball milled sample was not as high as that on the Li 2 CuO 2 solid state sample.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Yang et al proposed an alternative route to produce LS m by mechanical milling during 120 hours of LiOH·H 2 O and tetraethyl orthosilicate as raw materials. They observed that the formation of the LS m phase depended on milling time and concentration of raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…Some methods have been used to synthetize single-phase Li 2 Si 2 O 5 powders with desirable shape, but unfortunately, mixture products among bulk-like Li 2 SiO 3 , Li 2 Si 2 O 5 and SiO 2 , are often inevitably generated via solid-state reaction 17 , combustion approaches 18 and sol-gel method 19 . The residual Li 2 SiO 3 produced by these methods were too stubborn to transform into Li 2 Si 2 O 5 even using excessive molar ratios of Si/Li > 1 (stoichiometric ratio of Li 2 Si 2 O 5 = 1), due to Li 2 SiO 3 aggregates can be obtained easily at low temperature (~20 °C) and exhibit excellent thermal stability even after calcination at 900 °C 20 . Thus, the incomplete solid-phase reaction attributed to the dynamic deficiency of solid-state diffusion with a slow rate at later period, is the emphatic shortcoming for these routes.…”
mentioning
confidence: 99%